Report on paleontology ... ([publisher not identified], 1886)
CONTENTS.--[I] Brachiopoda and Lamellibranchiata of the Raritan clays and Greensand marls of New Jersey, by R. P. Whitfield. 1886.--[II] Gasteropoda and Cephalopoda of the Raritan clays and Greensand marls of New Jersey, by R. P. Whitfield. 1892.--III. The Paleozoic faunas, by Stuart Weller. 1903.--IV. Report on the cretaceous paleontology of New Jersey, by Stuart Weller. v. 2. 1907.